Relationship between the central government and local governments in the light of the centralized and decentralized administrative - سعيد هديل كاظم; العلاق عصام مجيد (Journal of Economics and Administrative Sciences, 2015)
Gaining the relationship between the central government and local governments is great importance especially after the expanded functions of the central government and became unable to carry out their works without all that delegate or transfer parts of its powers to lower levels. The aims of the research is to determine the relationship of the central government with the local government in accordance with the principle of administrative decentralization with the presentation of the competent authorities, the control of local governments, according to the Provincial Council Act No. 21 of 2008 amended. The research has a problem that has been the relationship of the central government to local governments in accordance with the Constitution and the law is different from what is applied on the ground and thus failure and reluctance to provide services and non-fulfillment of the local requirements. To understand the nature of the relationship between the central government and local governments to adopt variable was represented by four central dimensions (control, participation, independence, election. This research adopted a case study approach was used several methods to gather evidence and information, including checklists and personal interviews and observations from the field cohabitation in Baghdad Provincial Council, Rely on a range of ways to deal with census data, including frequency distribution and percentages to describe the variables of the study and diagnosis, the arithmetic mean to determine the level of response to the variables of the study test the sincerity scale manner ratios comparison, the results of the search Reached to a group of the most important conclusions was that the relationship between the central government and local governments, according to the constitution is a cooperative relationship coordinating give local governments autonomy in administrative and financial performance of its business without subjecting the control or supervision of the central government. Search and recommended the granting of the central government has the right of Administrative Control on the local government and the central control is an important element of administrative decentralization, where did not include the Constitution and the law state control of the central government to local government.